My cat does ballet - Heidbreder, Robert; Schu, Matt, 1993- (2023)
A boy compares the antics of his ballet cat with those of his friends, and invites them to bring their cats over to join in a Corp de Chat performance. Includes numerous ballet terms as well as information on famous dancers.
Ages 4 to 8.
Keywords: Cats -- Juvenile fiction; Pets -- Juvenile fiction; Ballet -- Juvenile fiction